Magnetic resonance imaging of the heart in the diagnosis of sarcoidosis - O V Stukalova; N V Meladze; D A Ivanova; T M Shvecz; S A Gaman; E A Butorova; R V Guchaev; M V Kostyukevich; S K Ternovoy (Терапевтический архив, 2018)
Heart sarcoidosis diagnosis presents great difficulties due to the absence of specific clinical manifestations. Most often, the diagnosis is established during autopsy. Magnetic resonance imaging (MRI) of the heart with contrast enhancement is one of the most informative methods of intravital diagnosis of cardiac sarcoidosis. In this article, two clinical cases, shows the role of MRI of the heart with contrast enhancement in the diagnosis of cardiac sarcoidosis.